2011
DOI: 10.1021/jp204504q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of [OH] Linkages on Luminescent Properties of ZnO Nanoparticles

Abstract: Abstract. Optical properties of ZnO nanoparticles prepared from a simple chemical method using sodium zincate bath show strong white light emission. X-ray absorption fine structure studies reveal a completely different local environment around Zn in these ZnO nanoparticles. The observed luminescence properties and local structural changes have been explained on the basis of a linkage between Zn and OH -ions in the surface layers of ZnO nanoparticles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The intensity loss of the green emission from the partially hydroxylated samples may have its origin in the annealing–induced annihilation of intrinsic bulk– or surface defects including the surface hydroxyls. , To address the latter possibility, we performed a control experiment by exposing the partially dehydroxylated Zn 0.3 Mg 0.7 O sample to air for 24 h (see Figures S2 in the Supporting Information). Subsequently, after being pumped down to <1 × 10 –6 mbar, the sample did not present a restoration of the PL emission observed before annealing.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity loss of the green emission from the partially hydroxylated samples may have its origin in the annealing–induced annihilation of intrinsic bulk– or surface defects including the surface hydroxyls. , To address the latter possibility, we performed a control experiment by exposing the partially dehydroxylated Zn 0.3 Mg 0.7 O sample to air for 24 h (see Figures S2 in the Supporting Information). Subsequently, after being pumped down to <1 × 10 –6 mbar, the sample did not present a restoration of the PL emission observed before annealing.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Among these, nano-zinc oxide (nano-ZnO) has been investigated due to its unique properties and potential applications as devices for spintronics or magnet-optics. [14][15][16][17][18] Several reports have been focused on the preparation of core-shell systems based on nano-ZnO and presenting high biocompatibility and high tolerance to cells (e.g. TiO 2 -coated ZnO 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The broadband detected at 3443 cm −1 is attributed to the stretching vibration mode of the hydroxyl group, which exists on the surface of the as-prepared Cr-doped ZnO nanoparticles [29]. The existence of the OH group in the samples is from the synthesis process and is linked to the zinc ion in the surface layers of the ZnO [30]. Giannakoudakis et al studied the role of terminal OH groups on zinc (hydr)oxides and observed that the hydroxyl groups cause a bandgap widening in the Zn(OH) 2 and ZnO [31].…”
Section: Resultsmentioning
confidence: 99%